Finite Element Analysis of Nonlinear Contact Problems with Mixed Eulerian-Lagrangian Description - Hariandja, Binsar Halomoan (President University, 2023)
This study deals with analysis of structures using mixed Eulerian-Lagrangian description. Apart from generally used Lagrangian description which uses initial configuration as reference, the newly proposed uses one of actual configuration as reference. Therefore, the total displacement is decomposed into two portions, i.e., the portion covering displacement from initial into referential configuration called Eulerian displacement, and the portion covering displacement from referential configuration into current configuration called Lagrangian displacement. The new technique is suitable to be applied to several classes of structures such as frictional contact and tensile structures. Eulerian displacement is used to represent relative displacements between material points paired in a nodal point in which slip mode occurs, while Lagrangian displacement is used to represent mutual displacement of material points paired in a nodal point in which stick mode occurs. The method was applied to certain contact problems, and the results obtained agreed fairly well with existing results found in references.